Penggunaan Pupuk Organik Pada Pertumbuhan Tanaman Tomat (Solanum Lycopersicum) Untuk Pelestarian Lingkungan - Rambulangi, Elisaberth (UNM Environmental Journals, 2017)
The purpose of this study was to determine how differences in crop growth and yield differences tomato (Solanum lycopersicum) of the two treatments, the use of organic fertilizers and inorganic fertilizers. This research is a type of action (action research), because the research is done to solve the problems associated with the theory of learning in the classroom, followed by conducting experiments carried out in the garden with the school experiment conducted two fertilization treatment, to observe the growth of tomato plants (Solanum lycopersicum ) so that this research also includes experimental research. The data collected in this study, in the form of numerical analyzed using statistics, thus including quantitative research, with data analysis techniques Pairet Samples T-Test. The results showed that there were significant differences between the two treatments, the treatment of first use of organic fertilizers represented variables X1, X2,  better than the secound treatments the use of chemical fertilizers (inorganic) are represented by variables Y1, Y2,  on the growth of tomato plants (Solanum lycopersicum).